Heterogeneous Fenton system driven by iron-loaded sludge biochar for sulfamethoxazole-containing wastewater treatment. (1st June 2023) - Liu, Liheng; Yu, Ronghao; Zhao, Shixiong; Cao, Xingfeng; Zhang, Xuehong; Bai, Shaoyuan
Abstract: In this study, the treatment performance of a heterogeneous Fenton system (Fe-BC + H2 O2 ) driven by iron-loaded sludge biochar (Fe-BC) on wastewater containing sulfamethoxazole (SMX) was investigated using the CODcr removal efficiency ( φ ) as an indicator. The batch experimental results showed that the optimal operating conditions were as follow: initial pH 3, H2 O2 concentration 20 mmol L −1, Fe-BC dose 1.2 g L −1, temperature 298 K. The corresponding φ was as high as 83.43%. The removal of CODcr was better described by BMG model and revised BMG (BMGL) model. According to the BMGL model, the φ max could be 98.37% (298 K). Moreover, the removal of CODcr was a diffusion-controlled process, while liquid film diffusion and intraparticle diffusion together determined its removal rate. The removal of CODcr should be a synergistic effect of adsorption and Fenton oxidation (real heterogeneous Fenton and homogeneous Fenton) and other pathways. Their contributions were 42.79%, 54.01% and 3.20%, respectively. For homogeneous Fenton, there seemed to be two simultaneous SMX degradation pathways: SMX→4-(pyrrolidine-11-sulfonyl)-aniline→N-(4-aminobenzenesulfonyl) acetamide/4-amino-N-ethyl benzene sulfonamides→4-amino-N-hydroxy benzene sulfonamides; SMX→N-ethyl-3-amino benzene sulfonamides→4-methanesulfonylaniline. In summary, Fe-BC had potential for practical application as a heterogeneous Fenton catalyst. Highlights: The removal efficiency of CODcr ( φ) at optimal conditions was 83.43% (298 K). The CODcr removal better followed BMGL model, and its φ max was 98.37% (298 K). The CODcr removal was relied on diffusion (liquid film & intraparticle diffusion). The contributions of adsorption and Fenton action were 42.79% and 54.01%. Homogeneous Fenton in solution had two simultaneous pathways for the SMX degradation.